An investigation of certain sixteenth and seventeenth century religious anxieties as a context for reading Shakespeare's "Troilus and Cressida" - Brand, Beth Anne (My University, 2016)
This dissertation explores the possibility of reading Troilus and Cressida in the context of the changing religious debate of the era, and certain differences to be found in protestant as compared with Catholic/Christian humanist discourses. [Abbreviated Abstract. Open document to view full version]
The dissertation submitted to the Faculty of Arts, University of the Witwatersrand, Johannesburg, for the degree of Master of Arts. Degree awarded with distinction on 6 December 1995